NOMINALISASI DAN PERAN SEMANTIK DALAM PODCAST JOE ROGAN “ISRAEL IS STARTING WW3” - Darmawan, Adhitya (Ma Chung Press, 2024)
This research focuses on nominalization, semantic roles or theta roles, and the functions of nominalizations in Joe Rogan’s Youtube Podcast entitled “Israel is Starting WW3”. This research is conducted based on two fundamental matters. The first one is that this research wants to reveal how the participants or speakers in the podcast create messages on this Israel-Palestine conflict since they are both American but one of them is middle-eastern mixed race. The second thing is due to the fact that there are still no research that combine the focus as what this research does which is the analysis of nominalizations, theta roles, and the functions of nominalizations. By combining these as the focus, this research aims to reveal not just on syntactic and semantic level but beyond those two approaches since this research also analyzes the functions of nominalization on the Podcast. This is a qualitative descriptive research for it’s data are multiple and holistically constructed and cannot be taken away from the context. In order to perform. The research findings show the total of 62 Data in both active and passive sentences. The findings also show that the roles are mostly agent-patient in active sentences and the functions are mostly to create framing of certain topic.